Sketching NLP: A Case Study of Exploring the Right Things To Design with Language Intelligence - Yang, Qian; Cranshaw, Justin; Amershi, Saleema; Iqbal, Shamsi; Teevan, Jaime (CHI 2019, 2019)
This paper investigates how to sketch NLP-powered user experiences. Sketching is a cornerstone of design innovation. When sketching designers rapidly experiment with a number of abstract ideas using simple, tangible instruments such as drawings and paper prototypes. Sketching NLP-powered experiences, however, presents unique challenges. It can be hard, for example, to visualize abstract language interaction, or to ideate a broad range of technically feasible intelligent functionalities. Via a frst-person account of our sketching process when designing intelligent writing assistance, we detail the challenges we encountered and describe emergent solutions such as a new format of wireframe for sketching language interactions and a new wizard-of-oz-based NLP rapid prototyping method. These findings highlight the importance of abstraction in sketching language interfaces and of designing within the capabilities and limits of NLP systems.